Acoso escolar en los y las adolescentes del Colegio Bernardo Valdivieso de Loja y su desempeño académico. - León Vidal, Radmila Stefanie (2013)
School harassment, also called bullying, it is a problem that comes from ancient times; however its studio is recent. This present research work is type descriptive, analytical and transversal, titled BULLYING IN THE TEENAGERS OF BERNARDO VALDIVIESO HIGH SCHOOL, whose main objectives were: to Identify the different types of bullying among adolescents in studio; to Know academic performance through scores of each student; to establish the relationship between bullying and academic performance in adolescents of Bernardo Valdivieso high school in Loja city, and propose an educational program for school adolescents about risks and consequences of bullying and their influences on academic performance we had obtained following results: Total sample was, 290 students who were administered the PRECONCIMEI (Avilés 2002) Questionnaire for the evaluation of students. (Adapted from Ortega, Mora-Merchan and Mora), 265 satisfied with inclusion criteria. The main results were: 32.83% suffer bullying and 67.17% don’t have this problem. From the first 70.11% were male and 29.89% female, in different modalities were presented, verbal harassment was about 46.41%, followed by physical with 35.47% and social with 25.28%, in respect academic performance the students that suffer bullying, we used grading scale by the Public Education Ministry of Ecuador which consists in Article 193 of Chapter III qualification and promotion, where we got that 74.71% of students reached Required Learning ( 7-8/10), 18.39% is next to achieving the Required Learning (5-6/10).